Phytotoxic effects of cigarette smoke on indoor plant Epipremnum aureum: in vivo analysis using chlorophyll a fluorescence transients - Garishma Shah; Upma Bhatt; Hanwant Singh; Hari Dev Chaudhary; Vineet Soni (Frontiers in Plant Science)
Indoor air pollution from cigarette smoke, poses significant threats to plant growth and development. This study investigates the impact of cigarette smoke on the indoor plant species Epipremnum aureum (money plant), focusing on morphological, biochemical, and physiological aspects, with an emphasis on photosynthetic efficiency. Plants were exposed to varying concentrations of cigarette smoke (0, 2, 4, 6, 8, 10 cigarettes/day) for 15 days in controlled conditions. Key findings include a significant reduction in the mean surface area (MSA) of leaves. Chlorophyll a fluorescence (ChlF) analysis revealed impaired PSII photochemistry, as evidenced by reduced fluorescence yields and a significant decrease in fluorescence intensity at higher smoke exposures. Specific energy fluxes, including absorption energy (ABS/RC), trapped energy (TR0/RC), and electron transport (ET0/RC), showed notable reductions, while dissipated energy (DI0/RC) increased significantly. The performance indices PIABS and PICS decreased with increasing smoke concentration and exposure duration, indicating a decline in overall photosynthetic efficiency. Principal component analysis demonstrated a distinct separation in the physiological response of plants based on exposure levels, with the highest cigarette smoke concentrations causing the most significant disruptions. The lethal dose calculations (LD50 = 6.4 cigarettes/day; LD90 = 9.9 cigarettes/day) highlight the severity of cigarette smoke’s impact on E. aureum. These results underscore the detrimental effects of cigarette smoke on indoor plants, suggesting that such pollutants can significantly impair plant health and stress the importance of managing indoor air quality.